2023
DOI: 10.3389/fanim.2023.1123532
|View full text |Cite
|
Sign up to set email alerts
|

In vitro screening of anti-methanogenic additives for use in Australian grazing systems

Abstract: Despite considerable effort to develop and optimise additives to reduce methane emissions from cattle, little information on additive effectiveness exists for cattle under grazing scenarios. As the majority of Australian cattle production occurs on grazing land it is pertinent to report on the use of additives under simulated conditions. The current study evaluated the addition of nine additives to Rhodes grass hay under in vitro conditions, to estimate their impact on methane (CH4), gas production, and rumen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In support, a meta-analysis showed that supplementation of Agolin ® Ruminants (coriander seed oil, eugenol, geranyl acetate, geraniol, and fumaric acid) produced no significant variation in the rumen pH of Holstein dairy cows [32]. On the contrary, several in vitro batch culture studies on individual or blends of essential oils, with or without fumaric acid, reported significant differences in ruminal pH [5,27,31,33]. Essential oils (EOs) have been reported to elevate rumen pH, either numerically [9,23] or significantly [15] when compared to control diets [31].…”
Section: Discussionmentioning
confidence: 99%
“…In support, a meta-analysis showed that supplementation of Agolin ® Ruminants (coriander seed oil, eugenol, geranyl acetate, geraniol, and fumaric acid) produced no significant variation in the rumen pH of Holstein dairy cows [32]. On the contrary, several in vitro batch culture studies on individual or blends of essential oils, with or without fumaric acid, reported significant differences in ruminal pH [5,27,31,33]. Essential oils (EOs) have been reported to elevate rumen pH, either numerically [9,23] or significantly [15] when compared to control diets [31].…”
Section: Discussionmentioning
confidence: 99%
“…Badgery et al [16] found that Biserrula pelecinus has great potential to reduce enteric CH 4 emissions, similarly to clover Trifolium subterraneum. Stifkens et al [51] found that increasing the proportion of legumes such as Leucaena leucocephala in feed reduces CH 4 due to condensed tannins acting as a bioactive compound that reduce methanogenesis. A 36% inclusion of Leucaena leucocephala in the diet of cattle reduced CH 4 by 25.09% per kilogram of boneless trimmed beef.…”
Section: Feed Formulationmentioning
confidence: 99%
“…Ridoutt et al [43] explored the supplement of Asparagopsis taxiformis, a red seaweed, on feedlot cattle's CH 4 production and calculated a 1-4% reduction in Australia's cattle sector. Parra et al [51] assessed a range of additives to reduce CH 4 in grazing cattle and found the addition of biochar and nitrate, biochar and Asparagopsis, and citral extract to significantly reduce CH 4 emissions by 22.83%, 19.82%, and 41%, respectively. Lean and Moate [20] reviewed CH 4 reduction strategies in Australia and found that nitrate supplementation reduced emissions by 10% and feed supplemented with 3-nitro-oxypropanol (3-NOP) reduced CH 4 by 22% in beef cattle and 39% in dairy cattle.…”
Section: Feed Supplements and Additivesmentioning
confidence: 99%
See 2 more Smart Citations